The Effectiveness of Chicken Liver Sausage Consumption on Increasing Hemoglobin and Iron Levels in Anemic Adolescent Girls in High School - Zuraida, Reni; Angraini, Dian Isti; Yunianto, Andi Eka; Ernawaty, Tutik; Meiyanti, Meiyanti; Yana, Risda (Fakultas Kedokteran, 2025)
Anemia in adolescent girls remains a public health problem in Indonesia. Low iron intake is a major contributing factor to anemia, while iron supplementation programs are not optimal due to low compliance. Chicken liver is a source of heme iron with high bioavailability, and sausage is a popular food product among adolescents. The purpose of this study was to assess the effectiveness of consuming selected formula chicken liver sausage on increasing hemoglobin and iron levels in anemic adolescent girls. This study used a quasi-experimental design with a pre-post test control group design conducted on 30 anemic female students divided into an intervention group (n=15) and a control group (n=14). The intervention group was given formula F6 chicken liver sausage for four weeks. Hemoglobin (Hb) and iron (Fe) levels were measured before and after the intervention. Analysis was performed using paired t-tests, Wilcoxon, and independent t-tests. The results showed a significant increase in Fe levels in the intervention group (Z = -2.272; p = 0.023), while the control group showed no significant changes (p = 0.272). Hb levels increased significantly in the control group (p = 0.002) but not in the intervention group (p = 0.057). Intergroup tests showed a significant difference in ΔFe (p = 0.026) but not in ΔHb (p = 0.308). Consumption of F6 formula chicken liver sausage effectively increased iron levels but did not significantly increase hemoglobin levels within the four weeks of intervention.